Does Lifestyle Mediate The Link Between Financial Literacy And Saving Behavior? Evidence From Lubuk Linggau University Students - Nengah Dewi Arianti; Herman Paleni; Rudi Azhar (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of financial literacy on students’ saving behavior and to examine the role of lifestyle as a mediating variable. A quantitative approach with a survey method was employed, targeting university students in Lubuklinggau City. The sample was determined using the Slovin formula with a 10% margin of error, resulting in 100 respondents. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both direct and indirect relationships among variables. The results indicate that financial literacy has a positive and significant effect on students’ saving behavior. This finding suggests that improved understanding and capability in managing personal finances encourage students to adopt better saving habits. In contrast, the mediation analysis reveals that lifestyle does not significantly mediate the relationship between financial literacy and saving behavior, indicating that the effect of financial literacy occurs directly. Financial literacy emerges as a key determinant in shaping sound financial behavior, particularly in saving practices. Although lifestyle is often associated with consumptive behavior, in this study it does not play a significant mediating role. This implies that students tend to manage their finances rationally without being dominantly influenced by their lifestyle. The findings imply that enhancing financial literacy should be a primary focus in promoting students’ saving behavior. Financial education, personal financial management training, and early saving habits can serve as effective strategies to improve the financial well-being of younger generations.